Current Role of Radiotherapy in the Management of Oral Cavity Squamous Cell Carcinoma. Issue 1 (March 2021) - Mendenhall, William M.; Holtzman, Adam L.; Dagan, Roi; Bryant, Curtis M.; Hitchcock, Kathryn E.; Amdur, Robert J.; Fernandes, Rui P.
Study Design: Literature review. Objective: To review the current role of radiotherapy (RT) in the management of oral cavity squamous cell carcinoma (SCC). Methods: Review of selected literature. Results: T1-T2N0 SCCs may be treated with either RT alone or surgery with a high likelihood of cure. The pendulum swung toward surgery with postoperative RT (PORT) added depending on the pathological findings in the mid 1980s. Patients with positive margins, extranodal extension (ENE), and/or 4 or more positive nodes receive concomitant chemotherapy (POCRT). Patients with T3-T4 and/or positive regional nodes are treated with surgery and PORT alone or POCRT. The likelihood of cure is moderate to low depending on extent of disease. The likelihood of major complications ranges from 10% to 30% depending on the method of reconstruction and the aggressiveness of postoperative PORT/POCRT. Patients with very advanced disease are treated with palliative RT, chemotherapy, or supportive care. Conclusions: The role of RT in the management of oral cavity SCC is primarily in the postoperative setting with palliative RT being reserved for those with very advanced disease where the likelihood of cure is remote.